PENDIDIKAN ISLAM PADA ANAK USIA DINI CIKAL BAKAL AKHLAK MULIA - Hasana, Dina; Aisyah, Siti (Proceeding International Seminar of Islamic Studies, 2024)
Every child born into the world by nature has a character obtained from parents and the environment. Therefore, education is very important for children through guidance given to children from birth to six years of age through educational stimulation support in the physical and spiritual growth and development of children by instilling correct and good principles in shaping children's behavior. A child has the right to receive education as the responsibility of parents because children are a gift given by Allah SWT. This study aims to provide an overview of Islamic education in early childhood as a forerunner to the formation of noble morals. This research uses qualitative research methods with literature studies to provide an overview of Islamic education conducted by parents as a forerunner to the formation of noble morals in early childhood. Data collection techniques are carried out through relevant research results from various journals of early childhood Islamic education, then added to the literature sources of early childhood education books. The result is that parents will understand how to educate children in accordance with the guidelines of the Koran. Especially educators at an early age in order to instill Islamic values from an early age so that later the forerunners of noble morals will grow from the behavior that has been fostered since